Passaging Primary Human Bronchial Epithelia Reduces CFTR-Mediated Fluid Transport and Alters mRNA Expression - Tongde Wu; Joe A. Wrennall; Hong Dang; Deborah L. Baines; Robert Tarran (Cells, 2023)
Primary human bronchial epithelial cultures (HBECs) are used to study airway physiology, disease, and drug development. HBECs often replicate human airway physiology/pathophysiology. Indeed, in the search for cystic fibrosis (CF) transmembrane conductance regulator (CFTR) therapies, HBECs were seen as the “gold standard” in preclinical studies. However, HBECs are not without their limitations: they are non-immortalized and the requirement for human donors, especially those with rare genetic mutations, can make HBECs expensive and/or difficult to source. For these reasons, researchers may opt to expand HBECs by passaging. This practice is common, but to date, there has not been a robust analysis of the impact of expanding HBECs on their phenotype. Here, we used functional studies of airway surface liquid (ASL) homeostasis, epithelial barrier properties, and RNA-seq and Western blotting to investigate HBEC changes over two passage cycles. We found that passaging impaired CFTR-mediated ASL secretion and led to a reduction in the plasma membrane expression of the epithelial sodium channel (ENaC) and CFTR. Passaging also resulted in an increase in transepithelial resistance and a decrease in epithelial water permeability. We then looked for changes at the mRNA level and found that passaging significantly affected 323 genes, including genes involved in inflammation, cell growth, and extracellular matrix remodeling. Collectively, these data highlight the potential for HBEC expansion to impact research findings.